Association between red blood cell distribution width and white matter hyperintensities: A large‐scale cross‐sectional study. Issue 9 (18th July 2020) - Wang, Meiyao; Feng, Hongliang; Zhang, Shuaimei; Luo, Zhengjin; Liang, Yan; Xu, Yan; Mei, Bin; Kong, Zhaohong; Liu, Yumin
Abstract: Background: Red blood cell distribution width (RDW) is a strong prognostic marker for various medical conditions, such as ischemic strokes. However, the relationships between higher RDW and the subtypes of white matter hyperintensities (WMHs) remain unclear. Hence, this study aimed to thoroughly evaluate the relationships between RDW and the subtypes of WMHs. Patients and methods: This cross‐sectional study was a retrospective analysis of hospital database (Dongguan Medical System, from April 2015 to February 2017). The presence and subtypes of WMHs were evaluated using Fazekas score with the T2WI‐FLAIR brain images from a 1.5‐T MRI system. The overall sample was randomly split in half. One of the two split‐half samples was used for determining the optimal cutoff value of higher RDW and another for further statistical analyses. Results: A total of 555 subjects with WMHs and 642 controls were recruited. The optimal cutoff value of higher RDW was 13.25%. Logistic regression revealed that higher RDW (≥13.25%) was positively associated with periventricular WMHs (adjusted OR = 1.81, 95% CI: 1.16–2.82, p  = .009). However, higher RDW was not associated with total WMHs (adjusted OR = 1.52, 95% CI: 0.99–2.33, p  = .057) and deep WMHs (adjusted OR = 1.21, 95% CI: 0.76–1.94, p  = .426). Conclusion: Our findings suggested that higher RDW may be independently associated with periventricular WMHs, but not with total WMHs and deep WMHs. Abstract : With the adequate sample size and comprehensive statistical analyses, our findings should be reliable and stable, which mainly suggest that higher RDW may be independently associated with the risk of WMHs and the risk of periventricular WMHs, but not with the deep WMHs.